DESCRIPTION OF A NEW CALOGLYPHUS BERLESE MITE (ACARI: ACARIDAE) INFESTING PULSES IN PAKISTAN - Sarwar, M.; Ashfaq, M. (The Nucleus, 2010)
Of the 13 mite species in genus Caloglyphus Berlese (family Acaridae) found in Pakistan, Caloglyphus arbelos was identified as a new species. The characters of apodeme 3 (ap3) which is reduced and broken medially enable the taxonomic separation of this new species from the other described taxa of genus Caloglyphus recorded from different geographical areas. A concise key on hypopus traits usable in taxonomy to discern this species from local and global specimens is made available. These studies on accurate diagnosis and identification of pest species are helpful in their successful management.